Pernikahan Kontrak dalam Perspektif Dekonstruksi Jacques Derrida - Elis Mila Rosa (Aqlania, 2023)
Different types of marriage have been found, one of which is contract marriage / mut'ah. In every country, the status of contract marriage is still in the zone of debate such as Iran, Arabia and Indonesia. The focus of this research is to try to analyze contract marriage by incorporating a theory from a famous figure, namely Jacques Derrida's deconstruction theory. The data collection technique used is qualitative which tends to use analysis. The result of the discussion in this study is that the use of Derrida's deconstruction is able to influence a person's thinking style when understanding a meaning then from the results of the meaning will not find a final context but will continue to be sustainable. Then another result with deconstruction is that the problem is not from who is right and wrong regarding the determination of the legal status of contract marriage, but rather looks at the community side, what is needed by the community. The conclusion of this study is that contract marriage according to Derrida's deconstruction is that understanding the contradictions of contract marriage is not seen from the law of marriage but from the needs of marriage.